New species of Hawaiian picture wing Drosophila (Diptera: Drosophilidae), with a key to species - Magnacca, Karl N.; Price, Donald K. (Zootaxa, 2012)
The picture wing species group of Hawaiian Drosophila is the only one to be relatively well known taxonomically, butspecies continue to be discovered. Here seven new species are described: Drosophila kikiko new species, Drosophila ki-noole new species, Drosophila moli new species, Drosophila nukea new species, Drosophila opuhe new species, Dros-ophila pihulu new species, and Drosophila pilipa new species. In addition, the male of Drosophila oreas Hardy isdescribed for the first time, and Drosophila virgulata Hardy & Kaneshiro is reduced to a new junior synonym of Dros-ophila lanaiensis Grimshaw, and the status of the latter and Drosophila ciliaticrus Hardy is clarified. A complete key to all the picture wing species is provided.